Mechanism Study on Radiosensitization Effect of Curcumin in Bladder Cancer Cells Regulated by Filamin A - Zhenfan Wang; Shuqing He; Minjun Jiang; Xue Li; Na Chen (SAGE Publishing, 2022)
Objective To study the radiosensitization effect of curcumin, a natural product with anti-inflammatory and anti-cancer properties, in bladder cancer cells and identify the specific role of FLNA gene in that process. Methods CCK-8 method was initially adopted to identify the proper interventional concentration of curcumin. T24 bladder cancer cells were subjected to CCK-8, flow cytometry, and colony formation assay to study the cell biological behaviors under different interventions. γ-H2AX test was performed to test the level of damage in T24 cells. RT-qPCR and Western blot were conducted to measure FLNA mRNA and protein levels. Results Low-dose curcumin (10, 20 μM) following X-ray exposure resulted in increased DNA damage, augmented apoptosis, and reduced proliferation of T24 cells. Certain radiosensitization was demonstrated when curcumin was applied at 10 μM. Additionally, elevation of FLNA gene and protein levels was also indicated upon combination treatment. Conclusion Low-dose curcumin has certain radiosensitization effect in bladder cancer, where FLNA plays a certain regulatory role.